2010
DOI: 10.2174/157016210793499187
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HIV Tropism in Ugandan Infants

Abstract: HIV-infected infants may have CXCR4-using (X4-tropic) HIV, CCR5-using (R5-tropic) HIV, or a mixture of R5-tropic and X4-tropic HIV (dual/mixed, DM HIV). The level of infectivity for R5 virus (R5-RLU) varies among HIV-infected infants. HIV tropism and R5-RLU were measured in samples from HIV-infected Ugandan infants using a commercial assay. DM HIV was detected in 7/72 (9.7%) infants at the time of HIV diagnosis (birth or 6–8 weeks of age, 4/15 (26.7%) with subtype D, 3/57 (5.3 %) with other subtypes, P=0.013).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Yet, it is unclear whether epidemiological factors, host factors, or viral properties were responsible (Hudgens et al 2002). There is also an epidemiological observation that subtype D viruses from Uganda and neighboring regions may show R5/X4 dual tropism more commonly than do other HIV-1 subtypes, but this may have a greater effect on viral pathogenesis than on transmission per se (Church et al 2010). Thus, unlike influenza virus in which ongoing genetic mutation dramatically impacts the frequency and patterns of virus transmission, such is not the case for pandemic HIV-1 group M viruses, which have been remarkably consistent in their transmissibility over expanses of time, geography, and target populations (Taylor et al 2008) and as the virus moved between individuals and groups of individuals with widely different risk behavior and virus transmission routes (Kouyos et al 2010).…”
Section: Epidemiology Of Hiv-1: Implications For Transmission Biologymentioning
confidence: 99%
“…Yet, it is unclear whether epidemiological factors, host factors, or viral properties were responsible (Hudgens et al 2002). There is also an epidemiological observation that subtype D viruses from Uganda and neighboring regions may show R5/X4 dual tropism more commonly than do other HIV-1 subtypes, but this may have a greater effect on viral pathogenesis than on transmission per se (Church et al 2010). Thus, unlike influenza virus in which ongoing genetic mutation dramatically impacts the frequency and patterns of virus transmission, such is not the case for pandemic HIV-1 group M viruses, which have been remarkably consistent in their transmissibility over expanses of time, geography, and target populations (Taylor et al 2008) and as the virus moved between individuals and groups of individuals with widely different risk behavior and virus transmission routes (Kouyos et al 2010).…”
Section: Epidemiology Of Hiv-1: Implications For Transmission Biologymentioning
confidence: 99%
“…In this study, the prevalence of CXCR4‐using viruses was highly observed in 119 (45%) out of 267 HIV‐1 infected children in Thailand, it was indicated this phenomenon is contrast with previously thought and suggested that vertical HIV‐1 infected children usually caused by R5 viruses . Previous study showed that vertically infected children harbored R5 virus at the time of diagnosis even their mothers carried X4 or R5 viruses .…”
Section: Discussionmentioning
confidence: 50%
“…HIV‐1 coreceptor usage has been broadly studied in HIV‐1 infected adults and few studies in the newborns or pediatric patients have been performed. Epidemiologic studies of HIV‐1 coreceptor usage among children in Uganda, Argentina, France, Spain, Italy, and India have shown that the distribution of HIV‐1 coreceptor usage is likely to be different because the majority of HIV‐1 infected children harbored R5 viruses, but some harbored X4 viruses . However, no data about HIV‐1 coreceptor usage in HIV‐1 infected children in Thailand have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn reduces viral spread from epithelial cells into virus-susceptible CD4+ T lymphocytes, CD68+ macrophages, and CD1c+ DC. The antiviral effect of hBD-2 PTD and/or hBD-3 PTD was independent of the tropism of HIV-1, suggesting that this approach may reduce HIV MTCT regardless of viral tropism [94][95][96][97].…”
Section: Discussionmentioning
confidence: 98%